Yield performance of new juice grape varieties grafted onto different rootstocks under tropical conditions - Silva, Marlon Jocimar Rodrigues da [UNESP]; Paiva, Ana Paula Maia [UNESP]; Pimentel, Adilson [UNESP]; Sánchez, Camilo André Pereira Contreras [UNESP]; Callili, Daniel [UNESP]; Moura, Mara Fernandes; Leonel, Sarita [UNESP]; Tecchio, Marco Antonio [UNESP] (Elsevier, 2018)
The objective of this work was to evaluate the yield components and physicochemical characteristics of bunches and berries of new grape varieties for juice elaboration, which were ‘Isabel Precoce’ (Vitis labrusca L.) and the hybrids ‘BRS Carmem’ ‘BRS Cora’ and IAC 138-22 ‘Máximo’ grown onto ‘IAC 572’ and ‘IAC 766’ rootstocks under tropical conditions. The yield components (number of bunches and yield per vine, as well as productivity) and the physicochemical characteristics of the bunches and berries of the eight scion-rootstock combinations were evaluated in three seasons. All data were subjected to analysis of variance and principal components analysis. The varieties ‘Isabel Precoce’ ‘BRS Cora’ and IAC 138 22 ‘Máximo’ produced high fruit yield, with the number of bunches and yield per vine similar to one another and superior to those of ‘BRS Carmem’. Significant differences occurred among varieties in the physicochemical grape characteristics. ‘Isabel Precoce’ and ‘BRS Carmem’ grapes had balanced levels of sugar and acid content, and ‘BRS Cora’ presented large bunches and berries, reaching high soluble solids content despite the high acidity. IAC 138-22 ‘Máximo’ grape also had large bunches but small berries and limited potential in the accumulation of sugars. The ‘IAC 766’ rootstock resulted in the best performance across all four varieties evaluated, showing maximum results in terms of fruit yield and physicochemical quality attributes of grapes.
Keywords: Grafting; Grape juice; Hybrid grapes; Tropical viticulture; Vitis labrusca L.